Analysis of Adhesion Quality of Mangium Laminated Wood with Polystirene Resin - Tito Sucipto; Surdiding Ruhendi (FORESTA, 2012)
Adhesion quality effeccted by adhesive and adheren quality, adhesion process, and product purpose condition. Materials in this research used mangium wood (Acacia mangium) and polystirene resin. The objective of the research was to know the adhesion quality of laminated wood and effect of fiber orientation (axial/ A; radial/ R; tangensial/ T), glue spread (120; 170 g/cm2) and glue spread system (single spread/ SS; double spread/ DS) to adhesion quality of laminated wood. The research results show that the highest of glue line shear strength are 5.01 N/mm2 (R–SS–170) for dry test, and 4.68 N/mm2 (T–SS–170) for wet test. Meanwhile the lowest of glue line shear strength are 1.47 N/mm2 (A–SS–120) for dry test, and 1.47 N/mm2 (T–SS–120) for wet test. Only two wet test laminated wood (T–SS–170 and T–SS–120) fulfill Indonesian standard/ SNI 06–6049–1999 (glue line shear strength ≥3 N/mm2).Keywords: glue line shear strength, mangium, glued laminated wood, polystirene resin